Pva-miR-252 participates in ammonia nitrogen-induced oxidative stress by modulating autophagy in Penaeus vannamei - Feifei Wang; Lin Huang; Meiqiu Liao; Wenna Dong; Can Liu; Xueqi Zhuang; Yuan Liu; Xiaoli Yin; Qingjian Liang; Weina Wang (Ecotoxicology and Environmental Safety, 2021)
MicroRNAs (miRNAs) are critical post-transcriptional regulators, which play a crucial role in resistance to adverse environmental stress by regulating autophagy. However, the mechanism of miRNA involved in the autophagy regulation of shrimp under ammonia nitrogen stress is still limited. In the present study, ammonia nitrogen could induce hepatopancreas injury and oxidative stress of P. vannamei, and significantly increase the content of ROS in hemocytes by flow cytometry. Simultaneously, it is accompanied by autophagy occurred in the hemocytes and hepatopancreas. Furthermore, the qRT-PCR analysis revealed that the expression of pva-miR-252 in P. vannamei decreased significantly after ammonia nitrogen stress, and pva-miR-252 negatively regulated PvPI3K by binding to 3′UTR of PvPI3K by double-luciferase assay. Pva-miR-252 overexpression could significantly increase the level of autophagy, and restore the autophagy inhibition caused by Chloroquine in vitro , whereas silencing of pva-miR-252 resulted in the opposite effect. More importantly, overexpression of pva-miR-252 could enhance the activity of antioxidant enzymes and reduced the production of ROS of shrimp under ammonia nitrogen stress. In conclusion, pva-miR-252 could positively regulate autophagy through PvPI3K and improve the antioxidant enzyme activity of P. vannamei under ammonia nitrogen stress, and our study provides a novel theoretical molecular mechanism for further understanding the shrimp cope with a high ammonia nitrogen environment.